Problem Kejiwaan Tokoh Utama dalam Novel Ayahku Bukan Pembohong Karya Tere Liye - Muhammad Fadilah Sidiq (Lembaga Pengembangan Kinerja Dosen, 2025)
Based on the formulation of the research problem, the main focus of this study is to analyze the psychological problems experienced by the main character in the novel Ayahku Bukan Pembohong by Tere Liye. The purpose of this study is to describe in depth the form of psychological problems that arise in the main character, especially in facing complex inner conflicts. The type of research used is descriptive qualitative with a foundation of Sigmund Freud's psychoanalytic theory that emphasizes three main aspects, namely the id, ego, and superego, as an analytical tool. The object of the research is the novel Ayahku Bukan Pembohong which displays the psychological dynamics of the main character through a storyline full of emotional tension. The character Dam is depicted experiencing an inner struggle due to feelings of hatred, regret, and rejection of the story told by his father, thus giving rise to an internal conflict that reflects the imbalance between subconscious drives and the reality he faces. The application of Freud's theory in this study was chosen because it is able to reveal how the inner anxiety and subconscious of the main character influence his behavior and attitudes in the story. This analysis reveals that the main character not only faces external conflict but is also threatened by ongoing internal psychological conflict, resulting in psychological behavior that demonstrates conflict between the impulsive id, the ego that tries to mediate, and the superego that demands adherence to values ​​and norms. This gives rise to psychological behavior.